2013
DOI: 10.1007/s11230-013-9444-5
|View full text |Cite
|
Sign up to set email alerts
|

Microcotyle omanae n. sp. (Monogenea: Microcotylidae), a parasite of Cheimerius nufar (Valenciennes) (Sparidae) from the Arabian Sea

Abstract: Microcotyle omanae n. sp. (Monogenea: Microcotylidae) is described from the gills of Cheimerius nufar (Valenciennes) (Sparidae) from the Arabian Sea. The new species closely resembles Microcotyle arripis Sandars, 1945, M. helotes Sandars, 1944, M. caudata Goto, 1984 and M. sebastis Goto, 1984, which have also been found in the Indo-Pacific. Microcotyle omanae n. sp. differs from M. arripis, M. helotes and M. caudata by its greater number of testes, from M. arripis, M. helotes by its greater length of the genit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A molecular study of the cox1 gene, unfortunately limited to a small number of samples, showed that the intraspecific distance was low (1.4%), especially when compared with distances between established species (10.2-15.0%). Intraspecific variations in body size in polyopisthocotylean monogeneans are well known, and the literature contains many examples of authors discussing artefacts of fixation and effect of flattening on the size of organs (Goto, 1894;Sproston, 1946;Justine, 2011;Machkewskyi et al, 2013). In Table 5, we compiled published results concerning the intraspecific differences of cox1 sequences.…”
Section: Intraspecific Morphometric and Molecular Variability In Polymentioning
confidence: 99%
See 2 more Smart Citations
“…A molecular study of the cox1 gene, unfortunately limited to a small number of samples, showed that the intraspecific distance was low (1.4%), especially when compared with distances between established species (10.2-15.0%). Intraspecific variations in body size in polyopisthocotylean monogeneans are well known, and the literature contains many examples of authors discussing artefacts of fixation and effect of flattening on the size of organs (Goto, 1894;Sproston, 1946;Justine, 2011;Machkewskyi et al, 2013). In Table 5, we compiled published results concerning the intraspecific differences of cox1 sequences.…”
Section: Intraspecific Morphometric and Molecular Variability In Polymentioning
confidence: 99%
“…During the 21st century, new genera (Omanicotyle Yoon, Al-Jufaili, Freeman, Bron, Paladini & Shinn, 2013, Paranaella Kohn, Baptista-Farias & Cohen, 2000 (see Kohn et al, 2000;Yoon et al, 2013) and species [Microcotyle algeriensis Ayadi, Gey, Justine & Tazerouti, 2017, M. argenticus Hadi & Bilqees, 2011, M. rubrum Hadi & Bilqees, M. jonii Hadi, Bilqees & Khatoon, 2011, M. omanae Machkewskyi, Dmitrieva, Al-Jufaili & Al-Mazrooei, 2013 and Polylabris bengalensis Sailaja & Madhavi, 2011] have been added to this family (Hadi & Bilqees 2010, 2011Sailaja & Madhavi, 2011;Machkewskyi et al, 2013;Ayadi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each host sample contained about 10-15 specimens, fresh fish were bought from landing sites or local fish markets and were immediately kept in cool bags and transported to the Laboratory of Aquatic Parasitology (Ministry of Agriculture and Fisheries Wealth, Oman). Fish were either freshly examined, kept in fridge during examination for at least 48 hrs or immediately frozen at -47°C for longer duration.The examination of fish and preparation of total mounts was carried out following the method of complete parasitological dissection and modified method of staining with acetic carmine [10,11]. Skin, gills, fins, abdominal organs, bits of muscles were removed, placed in seawater (or saline solution) and checked for parasites under a Zeiss Stemi 2000-C dissecting microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The worms collected were gently pressed between cover slip and glass slide and fixed using AFA (Acetic acid-Formalin-Alcohol) solution. Some of the cestodes were stained with Mayer's paracarmine [12], the others were stained with acetocarmine (Russian modification) [13], dehydrated using an ethanol series (80-100%) and mounted in Canada balsam.…”
Section: Methodsmentioning
confidence: 99%